The aphoristic character of Taras Melnychuk’s poetry: the stylistic and syntactic aspect - Калашник, Юлія Іванівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The article reveals the individual stylistic features of T. Melnychuk’s poetic language as represented in their semantic and syntactic organisation and stylistic functions. The task was to study the semantics of the aphorisms, their syntactic structure and stylistic means and to identify the compositional functions. According to the degree of the semantic dominant expression, the aphorisms of the analysed poetry are figurative and concentrate around the themes and motifs that have to do with Ukraine, its history, the destiny of the poet himself, with moral and ethical issues, with eternal values. The comprehensiveness of the aphoristic character of the analised poems is proved. T. Melnychuk’s aphoristic expressions are established to correlate with various syntactic constructions: from a simple sentence to overphrase unities. The registered poetic aphorisms are mostly equivalent to complex sentences of minimum structure with adverbial clauses of condition or cause as well as attributive clauses etc. The aphorisms are also represented by multicomponent complex sentences and coordinate constructions (the latter have mainly comparative-contrastive relations between the predicative parts) and, more seldom, by asyndetic sentences. Prevalence of the aphorisms equivalent to composite sentences and overphrase unities can be explained by their being not only sense-making but also compositional components of T. Melnychuk’s poems. There are whole strophes or poems of aphoristic character. T. Melnychuk’s aphoristics is characterised by folkloristic nature, by tending to maxims. The aphoristic character is based on paradoxical features and is created by various oppositions, repetitions, negation, chiasmus, is supported by rhyming.